The influence of glove type on simulated wheelchair racing propulsion: A pilot study - Rice, I.; Dysterheft, J.; Bleakney, A. W.; Cooper, R. A. (International Journal of Sports Medicine, 2016)
Our purpose was to examine the influence of glove type on kinetic and spatiotemporal parameters at the handrim in elite wheelchair racers. Elite wheelchair racers (n=9) propelled on a dynamometer in their own racing chairs with a force and moment sensing wheel attached. Racers propelled at 3 steady state speeds (5.36, 6.26 & 7.60?m/s) and performed one maximal effort sprint with 2 different glove types (soft & solid). Peak resultant force, peak torque, impulse, contact angle, braking torque, push time, velocity, and stroke frequency were recorded for steady state and sprint conditions. Multiple nonparametric Wilcoxon matched pair`s tests were used to detect differences between glove types, while effect sizes were calculated based on Cohen`s d. During steady state trials, racers propelled faster, using more strokes and larger contact angle, while applying less impulse with solid gloves compared to soft gloves. During the sprint condition, racers achieved greater top end velocities, applying larger peak force, with less braking torque with solid gloves compared to soft gloves. Use of solid gloves may provide some performance benefits to wheelchair racers during steady state and top end velocity conditions.